Utilizing the Bioecological Properties of Bryophytes in Environmental Biomonitoring: A Functional Approach - Nagmetullaev, Marat (American Journal of Botany and Bioengineering, 2025)
The pressing global need to monitor environmental health has led to the increasing integration of bioindicator species into environmental assessment frameworks. Among these organisms, bryophytes have emerged as particularly potent indicators due to their physiological sensitivity, surface-level exposure to environmental elements, and lack of cuticular barriers. While previous studies have emphasized their heavy metal accumulation capabilities, this article adopts a functional approach, focusing on how specific bioecological traits—such as water retention, nutrient cycling, and microbiome associations—enhance their value in comprehensive biomonitoring.